Aspects of Villa-Lobos’s Tonal Style in Some of His Studies for Guitar - Navia, Gabriel (Revista Vórtex, 2020)
The goal of this paper is to shed new light on selected strategies that characterize the tonal style of the first nine studies of the set by means of examining Villa-Lobos’s treatment of tonality from a perspective that takes into account the role of large-scale structure. I focus on three broad tonal effects that characterize the style of the selected studies, examining in detail some of their specific realizations. I demonstrate how 1) tonal madness may be associated with the deformation of tonic and dominant functions, 2) tonal ambiguity emerges from the presence of opposing tonal forces within the same musical space, and 3) tonal coloring is achieved through chromatic voice-leading, tonally oriented parallelism, and the substitution of standard tonal events. The theoretical foundation combines Schenkerian theory with aspects of Joseph Straus’s interdisciplinary studies on musical modernism and disability (2018) and Daniel Harrison’s harmonic theory on 19th- and early 20th-century chromatic music (1994).